Major cardiovascular events in patients with severe COPD with and without asthma: a nationwide cohort study. Issue 3 (26th September 2022) - Bonnesen, Barbara; Sivapalan, Pradeesh; Kristensen, Anna Kjær; Lassen, Mats Christian Højbjerg; Skaarup, Kristoffer Grundtvig; Rastoder, Ema; Sørensen, Rikke; Eklöf, Josefin; Biering-Sørensen, Tor; Jensen, Jens-Ulrik Stæhr
Background: Chronic low-grade inflammation as in asthma may lead to a higher risk of cardiovascular events. We evaluated whether patients with COPD and asthma have a higher risk of acute cardiovascular events than patients with COPD without asthma. Methods: Nationwide multicentre retrospective cohort study of Danish outpatients with a specialist diagnosis of COPD with or without asthma. Patients with both COPD and asthma were propensity-score matched 1:2 to patients with COPD without asthma. The primary end-point was severe major adverse cardiac events (MACE), defined as mortal cardiovascular events and events requiring revascularisation or hospitalisation. Results: A total of 52 386 Danish patients with COPD were included; 34.7% had pre-existing cardiovascular disease, and 20.1% had asthma in addition to their COPD. Patients with pre-existing cardiovascular disease were then propensity-score matched: 3690 patients with COPD and asthma versus 7236 patients with COPD without asthma, and similarly, for patients without pre-existing cardiovascular disease (6775 matched with 13 205). The risk of MACE was higher among patients with asthma and COPD versus COPD without asthma: hazard ratio (HR) 1.25 (95% CI 1.13–1.39, p<0.0001) for patients with pre-existing cardiovascular disease and HR 1.22 (95% CI 1.06–1.41, p=0.005) for patients without pre-existing cardiovascular disease. Conclusion: Among patients with COPD, asthma as a comorbid condition is associated with substantially increased risk of cardiovascular events. The signal was an increased risk of 20–25%. Based on our study and other smaller studies, asthma can be considered a risk factor for cardiovascular events among COPD patients. Among patients with COPD and pre-existing cardiovascular disease, asthma as a comorbid condition is associated with substantially increased risk of cardiovascular events. https://bit.ly/3uEtA3r